Experimental series and use-wear in bone tools - Buc, Natacha (2011)
This paper presents an experimental program and microscopic patterns identified in the analysis of five worked bone morpho-functional groups: harpoon heads, drilled points, bipoints, awls and smoothers. Considering the common use hypotheses of each tool, the experimental program involved manufacture and use in impact, hafting, piercing and smoothing activities performed on animal carcasses, wood, skin, silica-rich plants and pottery. Not only a microscopic database of these hypothetical activities was obtained, but also it was tested the efficiency of tools to meet those mechanical requirements. As other authors working on bone use-wear have previously asserted, each activity and material leaves particular use-wear patterns. Comparing my results with those of preexisting publications, I attempt to develop a general database useful to analyze archaeological bone tools.